Biosynthesis and characterization of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer from wild type Comamonas sp. EB172. - Zakaria, Mohd Rafein; Ariffin, Hidayah; Mohd Johar, Noor Azman; Abd. Aziz, Suraini; Nishida, Haruo; Shirai, Yoshihito; Hassan, Mohd Ali (Elsevier, 2010)
Poly(3-hydroxybutyrate) [P(3HB)] homopolymer and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] copolymer was produced by Comamonas sp. EB172 using single and mixture of carbon sources. Poly(3-hydroxyvalerate) P(3HV) incorporation in the copolymer was obtained when propionic and valeric acid was used as precursors. Incorporation of 3HV fractions in the copolymer varied from 45 to 86 mol% when initial pH of the medium was regulated. In fed-batch cultivation, organic acids derived from anaerobically treated palm oil mill effluent (POME) were shown to be suitable carbon sources for polyhydroxyalkanoate (PHA) production by Comamonas sp. EB172. Number average molecular weight (Mn) produced by the strain was in the range of 153–412 kDa with polydispersity index (Mw/Mn) in the range of 2.2–2.6, respectively. Incorporation of higher 3HV units improved the thermal stability of P(3HB-co-3HV) copolymer. Thus the newly isolated bacterium Comamonas sp. EB172 is a suitable candidate for PHA production using POME as renewable and alternative cheap raw materials.